Impact Detection and Characterization in Composite Laminates with Embedded Fiber Bragg Gratings. (2017) - Yeager, Michael; Whittaker, Anthony; Todd, Michael; Kim, Hyonny; Key, Chris; Gregory, William
Abstract: The use of composite materials has expanded significantly across civil, aerospace, and marine structures in both new designs and retrofits. The performance benefits from composites–typically, weight reduction with increased strength, corrosion resistance, and improved thermal and acoustic properties–are challenged by a host of failure modes whose genesis and progression aren't yet well understood. As such, structural health monitoring (SHM) plays a key role for in-situ assessment for the purposes of performance/operations optimization, maintenance planning, and overall life cycle cost reduction. In this work, arrays of fiber Bragg grating optical strain sensors are embedded into a pre-preg composite specimen that was designed by surrogate finite element model simulation, and will be subjected to both low-energy (non-damaging) impacts at various locations and high-energy damaging impacts at a known location. The impactor was designed along with the panel specimen for very specific energy levels, strain frequency, and strain amplitude response. Results from SHM algorithms developed via hypothesis testing are demonstrated on blind impact tests in order to determine the efficacy of embedded fiber Bragg grating arrays for assessing structural health of such composites.